Menjelajahi Perkembangan Fungsi Otak Anak Usia Dini: Pendampingan Di KB Pelita Hati Bakuan - Kartika Fajriani; Lailatul Hidayah; Dini Dwi Junistira; Nova Anggraeni (CV. Multi Kreasi Media, 2024)
Study of brain function development in early childhood in the context of community service in KB Pelita Hati Bakuan. This study aims to improve teachers' and parents' understanding of the importance of proper monitoring and stimulation of early childhood brain function development. However, in its application, problems arise, teachers experience problems in terms of recognizing children's brain function and are less able to identify student development. The solution to the problems faced by teachers and parents is to provide knowledge about recognizing the development of children's brain function and providing appropriate stimuli to help child development. This research helps educators facilitate the development of children's brain function potential optimally and build good cooperation between teachers and parents to support children's academic development. The research method used is a survey and data collection from related literature. The results showed an improvement, shown from the results of the pree-test initially achieved 60%, and after being given training and understanding, the post-test achieved the target of 95% of the 16 (sixteen) participants who participated, there was a significant increase in participants by 35% after participating in training activities. Thus, collaboration between experts, parents, and communities in providing the resources and support needed to improve the quality of early childhood education. This Community Service Research emphasizes the need for a holistic approach to supporting the optimal development of children's brains, as well as the importance of increasing public awareness of their role in creating an environment that supports children's growth and development.